Value of National Cultural Dimension of Social Entrepreneurship in Indonesia - Cahayani, Ati; Gunawan, Aristo Surya; Khafian, Nidaan (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
Social entrepreneurship in Indonesia has multiplied. They are more public figures in the field of social entrepreneurship. The fundamental value that made them set up social entrepreneurship is caring. However, it assumed that those specific fundamental values make social entrepreneurship in Indonesia unique. These values reflect the national cultural dimensions of social entrepreneurship in Indonesia. This study wants to analyze whether the national cultural dimensions of the seven organizations are identical using a qualitative method for analyzing secondary and primary data. Primary data were obtained from interviews with seven owners or leaders of the social enterprises, and the sampling technique used was purposive sampling. Secondary data were obtained from those seven social enterprises' literature or the official site. The method of analysis that was used is content analysis. The finding is that the founders' values influence five national cultural dimensions in those seven organizations.